Quality of life in older adults: Benefits from the productive engagement in physical activity - Hsin-Yen Yen; Li-Jung Lin (Elsevier, 2018)
Background/objective: Productive engagement can be a strategy to reduce stress and chaos. Physical activity, a basic type of productive activity, could benefit older adults. Therefore, the purpose of this study was to explore how productive engagement in physical activity may influence older adults in maintaining their health-related quality of life when they live in a long-term care facility. Methods: We used purposive sampling to recruit 163 participants from 14 long-term care facilities in Taiwan. Data were collected through individual interviews with a structured questionnaire. Descriptive statistics and independent t-test were used. Results: The result demonstrated that the preferred type of physical activities for the older adults was similar after the relocation. Older adults with increasing productive engagement in physical activity reported better scores of Mental Component Summary, social and emotional role functioning than those with decreasing productive engagement in physical activity. Conclusion: Older adults can have a positive perceived health-related quality of life by consistently or increasingly engaging in productive physical activity, especially when encountering a life event. Keywords: Exercise, Mental health, Long-term care, Relocation, Successful aging